Gender dysphoria in children and adolescents - a disease far from pediatric practice? - Mirela Silvia Iancu; Ana-Maria Davitoiu; Sorina Chindris; Iulia Florentina Tincu; Monica Livia Gheorghiu; Doina Anca Pleşca (Amaltea Medical Publishing House, 2020)
Gender dysphoria is not a condition that the Romanian pediatrician commonly encounters in his/her practice. However, in light of the progress made in order to diagnose early and establish a correct treatment, as well as in the evolving context of society, including the one of our country, medical cases will not be long in coming. This paper aims to briefly review, the main characteristics of the disease and the role that the pediatrician can play in the life of the patient already diagnosed or not yet, with gender dysphoria.